2010
DOI: 10.1111/j.1439-0434.2010.01688.x
|View full text |Cite
|
Sign up to set email alerts
|

Mango Malformation Disease in South China Caused by Fusarium proliferatum

Abstract: A total of 13 Fusarium isolates were obtained from samples of malformed mango seedlings from Yunnan and Sichuan provinces in China, and five morphologically similar isolates were confirmed causing the disease by satisfying KochÕs postulates. One typical isolate (MG4) was selected for detailed morphological and molecular studies. Based on the following morphological characteristics, isolate MG4 was identified as Fusarium proliferatum: white aerial mycelium on PSA (potato sucrose agar: potato 200 g; sucrose 15 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Recently, in Yunnan and Sichuan provinces, China, it has been known as the causal agent of malformation disease of mango (Zhan et al. ). However, to the best of our knowledge, this is the first report of F. proliferatum infecting carnation ( Dianthus caryophyllus L.) in China.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, in Yunnan and Sichuan provinces, China, it has been known as the causal agent of malformation disease of mango (Zhan et al. ). However, to the best of our knowledge, this is the first report of F. proliferatum infecting carnation ( Dianthus caryophyllus L.) in China.…”
Section: Resultsmentioning
confidence: 99%
“…The fruit of mango ( Mangifera indica L.) is exceptional for its spicy, succulent, thick fruit pulp and abundant nutrients, containing a wide range of amino acids, sugar, organic acids, and minerals including Ca, P, Fe, and K as well as a great variety of vitamins. Mango cultivation is affected by specific constraints, among which mango malformation disease (MMD) caused by Fusarium mangiferae is considered to be one of the most important threats in the majority of mango-planting regions worldwide (Ploetz et al, 2002 ; Marasas et al, 2006 ; Zhan et al, 2010 , 2012 ). In the past decade, MMD has destroyed many thousands of hectares of mango in tropical and subtropical countries.…”
Section: Introductionmentioning
confidence: 99%
“…It can be concluded that F. proliferatum is the causal pathogen of vegetative malformation of coconut palms in southern Iran. F. proliferatum has been previously reported from Egypt, Malaysia and China as the causal pathogen of mango malformation disease (Haggag & El‐Wahab, ; Mohamed Nor et al, ; Zhan et al, ); however, in Malaysia, this species has not been reported to cause any malformation symptoms on the artificially inoculated mango seedlings (Mohamed Nor et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Malformation caused by Fusarium species is an important and destructive plant disease which, to our knowledge, has been documented only on mango trees in most mango‐producing countries of Asia, Africa and America (Crespo et al, ). Several Fusarium species in the Gibberella fujikuroi species complex, including Fusarium mangiferae (Crespo et al, ; Gamliel‐Atinsky, Sztejnberg, Maymon, Shtienberg, & Freeman, ; Gamliel‐Atinsky, Sztejnberg, Maymon, Vintal, et al, ; Noriega‐Cantú et al, ; Sinniah et al, ; Zhan et al, ), F. proliferatum (Haggag & El‐Wahab, ; Mohamed Nor, Salleh, & Leslie, ; Zhan et al, ), F. sterilihyphosum (Britz et al, ; Steenkamp et al, ), F. mexicanum (Otero‐Colina et al, ), F. pseudocircinatum (Freeman et al, ) and F. tupiense (Crespo et al, ; Lamine, Sharma, Lava Kumar, & Bandyopadhyay, ), have been identified to be associated with vegetative and floral malformation disease of mango. Malformation affects both vegetative and reproductive tissues of the host plants.…”
Section: Introductionmentioning
confidence: 99%